Dampak Migrasi Dan Upah Minimum Provinsi Terhadap Pengangguran Terdidik Di Indonesia - Okta Mulyana Ilhami; Yeniwati Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to find out & analyze; (1) To what extent is the impact of inbound migration on unemployment with graduates of junior high school, high school & university in Indonesia, (2) What is the impact of the provincial minimum wage on unemployment with graduates of junior high school, high school & university in Indonesia, ( 3) To what extent is the impact of in-migration and the provincial minimum wage on educated unemployment who graduated from junior high school, high school and university in Indonesia. This research is a narrative & inductive type of research. The data used is secondary panel data for 33 provinces in Indonesia according to 2010-2019 obtained from related forums and then analyzed using panel regression examples by testing classical estimates. The results of the study show that simultaneously, in-migration and the provincial minimum wage have a significant impact on educated unemployment who graduated from junior high school, high school and university in Indonesia. Furthermore, partially (1) in-migration has a negative & insignificant effect on unemployment with junior high school graduates in Indonesia (2) the provincial minimum wage has a negative & significant effect on unemployment with junior high school graduates in Indonesia (3) in-migration has a negative & significant effect on not significant on unemployment with high school graduates in Indonesia (4) the provincial minimum wage has a positive and significant effect on unemployment with high school graduates in Indonesia (5) in-migration has a positive and significant effect on unemployment with college graduates in Indonesia (6) The provincial minimum wage has a negative and insignificant effect on educated unemployment for university graduates in Indonesia. In the future, it is recommended that the government put the expansion of employment opportunities as a result of which it can balance according to the rate of population growth. Through the central government, the government in each province needs to provide skills and skills to the people so that job seekers who do not have good skills and skills can permanently compete for jobs.